2018
DOI: 10.1101/259499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convergent evolution of gene expression in two high-toothed stickleback populations

Abstract: 25Changes in developmental gene regulatory networks enable evolved changes in morphology. 26These changes can be in cis regulatory elements that act in an allele-specific manner, or 27 changes to the overall trans regulatory environment that interacts with cis regulatory 28 sequences. Here we address several questions about the evolution of gene expression 29 accompanying a convergently evolved constructive morphological trait, increases in tooth 30 number in two independently derived freshwater populations of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 69 publications
2
20
1
Order By: Relevance
“…If we assume that the majority of the eQTLs on the same chromosomes are putatively cis ‐regulatory mutations, as reported in a previous study (Ponsuksili, Murani, Schwerin, Schellander, & Wimmers, ), our data suggest that cis ‐regulatory mutations contribute more to the transcriptome evolution between ecotypes than trans ‐regulatory mutations. This contrasts with a previous work on the stickleback dental tissues, indicating that the contribution of trans ‐regulatory mutations is larger than cis ‐regulatory mutations to parallel gene expression changes (Hart et al., ). Further analysis on tissues other than brains and dental tissues would help to understand whether different tissues have different mechanisms underlying parallel transcriptome evolution.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…If we assume that the majority of the eQTLs on the same chromosomes are putatively cis ‐regulatory mutations, as reported in a previous study (Ponsuksili, Murani, Schwerin, Schellander, & Wimmers, ), our data suggest that cis ‐regulatory mutations contribute more to the transcriptome evolution between ecotypes than trans ‐regulatory mutations. This contrasts with a previous work on the stickleback dental tissues, indicating that the contribution of trans ‐regulatory mutations is larger than cis ‐regulatory mutations to parallel gene expression changes (Hart et al., ). Further analysis on tissues other than brains and dental tissues would help to understand whether different tissues have different mechanisms underlying parallel transcriptome evolution.…”
Section: Discussioncontrasting
confidence: 95%
“…If the contribution of the parallel evolution of gene expression to phenotypic convergence is prevalent, we can predict that many genes would be repeatedly up‐ or down‐regulated in one ecotype compared to another in independent lineages. Consistent with this prediction, some of the previous transcriptome studies showed parallel transcriptome evolution between the low‐ and the high‐latitude populations of Drosophila melanogaster and D. simulans and between the marine and freshwater ecotypes of stickleback (Hart, Ellis, Eisen, & Miller, ; Zhao, Wit, Svetec, & Begun, ). However, other studies failed to show significant parallel patterns between the wild and weedy populations of Helianthus annuus (Lai, Kane, Zou, & Rieseberg, ) or revealed not only parallel, but also antiparallel patterns (i.e., ecotypes in different lineages showed opposite direction of differential expression) between the normal and dwarf morphs of whitefish (Derome, Duchesne, & Bernatchez, ) and between the lake and stream ecotypes of stickleback (Hanson, Hu, Hendry, & Barrett, ).…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…(2015) demonstrated substantial heritability of genome‐wide gene expression variation in a three‐spined stickleback population from the Baltic Sea. Likewise, the genetic basis of gene expression variation has been recently uncovered in several three‐spined stickleback populations (Hart, Ellis, Eisen, & Miller, 2018; Pritchard et al., 2017). Notably, trans ‐regulatory changes are predominant and more likely to be shared among convergently evolved populations, whereas different cis ‐regulatory changes are more frequent in convergently evolved populations (Hart et al., 2018).…”
Section: Discussionmentioning
confidence: 99%